2019
DOI: 10.1016/j.jadohealth.2018.10.029
|View full text |Cite
|
Sign up to set email alerts
|

15. Positively Connected For Health (PC4H): Acceptability And Feasibility of A Digital Health Adherence And Engagement In Care Intervention For Adolescents And Young Adults Living With HIV

Abstract: SBHC staff, and use of performance improvement tools led by an Implementation Coach) and staff-level initiatives (trainings, technical assistance and incentives). Three matched-pairs of SBHCs were assigned to two cohorts to receive the same intervention: Cohort 1 initiated in Fall 2016, Cohort 2 in Fall 2017. All patients seen at least once in baseline and intervention years were included for analysis. Outcomes were the offer of an annual HIV test by the clinical staff and the acceptance of testing by the adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Below, we report details of the PEERNaija development process, as well as the resulting product based on the IDEAS phases, with each phase used to inform the next step of the development process. (32)(33)(34) for AYA-HIV in the US, and data from systematic reviews highlighting barriers to medication adherence guided the Empathize phase of the development process (4-6, 8). Dr. Ahonkhai's preliminary quantitative data demonstrated that 40% of Nigerian AYA-HIV who remained in care 1 year after starting ART had virologic failure (HIV RNA > 1,000 copies/mL) (4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Below, we report details of the PEERNaija development process, as well as the resulting product based on the IDEAS phases, with each phase used to inform the next step of the development process. (32)(33)(34) for AYA-HIV in the US, and data from systematic reviews highlighting barriers to medication adherence guided the Empathize phase of the development process (4-6, 8). Dr. Ahonkhai's preliminary quantitative data demonstrated that 40% of Nigerian AYA-HIV who remained in care 1 year after starting ART had virologic failure (HIV RNA > 1,000 copies/mL) (4).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative insights into the needs and thought processes of AYA-HIV were gathered from formative, in-depth interviews from Nigerian AYA-HIV, as well as by Dowshen et al through the development of the TreatYourSelf mHealth application (32)(33)(34). Ahonkhai conducted semi-structured in-depth interviews with 20 AYA-HIV at the study site, NIMR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations